Les révolutions arabes entre césures et remembrances : tiers-mondisme, question palestinienne et utopies chiliastiques - Nicolas Dot-Pouillard (L’Année du Maghreb)
The revolutionary and insurrectionary eventness deployed in the Arab world since January 2011 did have, to some extent a degree of “newness” : analysts and researchers have basically endeavored to identify its manifestations in the radical appropriation of the democratic paradigm by Egyptian, Libyan or Tunisian insurgents, in the use of new globalized computer technologies, and in the absence - at least in the early stages - of seminal ideology, even of duly established leaderships in the uprisings. The radical novelty of these revolutionary processes may even have established fundamental breaking points from elements that were associated to the concept of “revolution” in the Arab world throughout the twentieth century, such as the common underlying notion of Third World, the commitment to the Palestinian cause, and finally the chiliastic and revolutionary dimension of revolutionary upheavals such as they were envisioned at that time. However the break appears to be relative : indeed a singular unresolved dialectic also seems to emerge between these different elements, where the past may sometimes serve as a reference updated in the face of “newness” whose contours and divides are gradually taking shape.